Absence of hyperexcitability of spinal motoneurons in patients with amyotrophic lateral sclerosis. (26th October 2019) - Marchand‐Pauvert, Véronique; Peyre, Iseline; Lackmy‐Vallee, Alexandra; Querin, Giorgia; Bede, Peter; Lacomblez, Lucette; Debs, Rabab; Pradat, Pierre‐François
Abstract : Key points: Amyotrophic lateral sclerosis (ALS) motoneurons become hypoexcitable with disease progression in experimental models, raising questions about the neural hyperexcitability supported by clinical observations. A variant of the ∆ F method, based on motor unit discharge frequency modulations during recruitment and derecruitment, has been developed to investigate the motoneuron capacity to self‐sustained discharge in patients. The modulation of motor unit firing rate during ramp contraction and vibration‐induced recruitment are modified in ALS, suggesting lower motoneuron capacity to self‐sustained discharge, which is a sign of hypoexcitability. ∆ F‐D decreases with functional impairment and its reduction is more pronounced in fast progressors. In patients with ALS, motoneurons exhibit hypoexcitability, which increases with disease progression. Abstract: Experimental models have primarily revealed spinal motoneuron hypoexcitability in amyotrophic lateral sclerosis (ALS), which is contentious considering the role of glutamate‐induced excitotoxicity in neurodegeneration and clinical features rather supporting hyperexcitability. This phenomenon was evaluated in human patients by investigating changes in motor unit firing during contraction and relaxation. Twenty‐two ALS patients with subtle motor deficits and 28 controls performed tonic contractions of extensor carpi radialis, triceps brachialis, tibialis anterior and quadriceps, aiming to isolate a low‐threshold unit (U1) on the electromyogram (EMG). Subsequently, they performed a stronger contraction or tendon vibration was delivered, to recruit higher threshold unit (U2) for 10 s before they relaxed progressively. EMG and motor unit potential analyses suggest altered neuromuscular function in all muscles, including those with normal strength (Medical Research Council score at 5). During the preconditioning tonic phase, U1 discharge frequency did not differ significantly between groups. During recruitment, the increase in U1 frequency (∆ F‐R ) was comparable between groups both during contraction and tendon vibration. During derecruitment, the decrease in U1 frequency (∆ F‐D ) was reduced in ALS regardless of the recruitment mode, particularly for ∆ F‐R  <8 Hz in the upper limbs, consistent with the muscle weakness profile of the group. ∆ F‐D was associated with functional disability and its reduction was more pronounced in patients with more rapid disease progression rate. This in vivo study has demonstrated reduced motoneuron capacity for self‐sustained discharge, and further supports that motoneurons are normo‐ to hypoexcitable in ALS patients, similar to observations in experimental models. Key points: Amyotrophic lateral sclerosis (ALS) motoneurons become hypoexcitable with disease progression in experimental models, raising questions about the neural hyperexcitability supported by clinical observations. A variant of the ∆ F method, based on motor unit discharge frequency modulations during recruitment and derecruitment, has been developed to investigate the motoneuron capacity to self‐sustained discharge in patients. The modulation of motor unit firing rate during ramp contraction and vibration‐induced recruitment are modified in ALS, suggesting lower motoneuron capacity to self‐sustained discharge, which is a sign of hypoexcitability. ∆ F‐D decreases with functional impairment and its reduction is more pronounced in fast progressors. In patients with ALS, motoneurons exhibit hypoexcitability, which increases with disease progression.